Hostility in the Real World and Online: The Effect of Internet Addiction, Depression, and Online Activity. - Yen, Ju-Yu; Yen, Cheng-Fang; Wu, Hsiu-Yi; Huang, Chun-Jen; Ko, Chih-Hung (CyberPsychology, Behavior & Social Networking, 2011)
Hostility online has not been evaluated by an empirical investigation. This study aims to evaluate (a) the difference between hostility in the real world and that online and (b) whether the difference is associated with Internet addiction, depression, or online activities. A total of 2,348 college students (1,124 males and 1,224 females) were recruited and completed the Chen Internet Addiction Scale, the Center for Epidemiological Studies' Depression Scale, and the questionnaire for online activity. Further, the Buss-Durkee Hostility Inventory-Chinese version-short form was utilized to evaluate hostility in both real and virtual worlds. The results demonstrated that the levels of all four dimensions of hostility were lower when getting online than those in the real world. Subjects with Internet addiction had higher hostility both in the real world and online as do subjects with depression. Further, college students with Internet addiction had increased expressive hostility behavior and those with depression had decreased hostility cognition, hostility affection, and suppressive hostility behavior when getting online. Lastly, the buffering effect of the Internet on hostility was attenuated among subjects paying the most online time in chatting, and those using the Internet mainly for online gaming had higher expressive hostility behavior not only in the real world but also online. These results suggest that attention should be paid to interventions concerning aggressive behavior among subjects with Internet addiction or online gaming and chatting. On the other hand, depressed college students would be less hostile after entering the Internet. It is suggested that the Internet would be one possible interactive media to provide intervention for depression.